Arctic lake transient electromagnetic (TEM) soundings 2016-2017 ... - Parsekian, Andrew; Creighton, Andrea; Jones, Benjamin; Bondurant, Allen; Arp, Christopher (Arctic Data Center, 2018)
This dataset contains transient electromagnetic (TEM) geophysical soundings acquired on Arctic lakes during spring fieldwork 2016 - 2017. Several additional TEM soundings are included acquired on terrestrial permafrost near lakes (for control) or historic boreholes (for validation). Measurements were made using an ABEM WalkTEM with a 1600m^2 transmitter loop, a 200m^2 receiver loop, and a 5m^2 receiver loop, all in a center-nested configuration. Raw data for 86 soundings are provided in the Universal Sounding Format (USF), and results after processing (smooth constraint) with ViewTEM (GuidelineGeo/ABEM/Aarhus Hydrogeopyhsics) inversion software are included as tabular geolocated values. A KML indicating point location of the center of each sounding is also provided. ...